Correlation between SPT and JKR Probe / Nor Azah Mohd Ali - Mohd Ali, Nor Azah (1990)
In-situ techniques of soil strength measurement such as Standard Penetration Test and JKR Probe Test are usually used in site investigation. This study tries to correlate the SPT N value and JKR Probe value ( blows / feet ) of clay & silt and silt & sand type of soils. ITM projects at Arau, School of Hotel and Catering Shah Alam and Additional Building Phase IB of Dungun campus are selected in determining the required soil data. Geological profile of each site is plotted to get the preliminary view of soil condition. Soil properties such as water content, consistency limit and grain size are determined. Regression analysis are made for SPT N value versus JKR Probe value correlation. Variables influencing both tests are listed. Some recomendations are proposed in getting better result and to continue this study in future.